Change of Animal Production in Samsun Province Between 2010 and 2020 - Savaş Atasever (Turkish Journal of Agriculture: Food Science and Technology)
Samsun is the most important province of the Black Sea Region by the socio-economic structure. In this study, how animal production changed between 2010 and 2020 in the province and the needed suggestions for the later period were revealed. In the assesment period of the study, an important increment occurred in the number of large and small animals except for equidae including horse, donkey and mule. Similarly, a high elevation of milk production in bovine, ovine, and goat has been observed in the province. While the floating structure in the number of poultry and honey production of the province has been noticed within the last decade, it may be declared that the animal production level of Samsun is generally better than the neighboring provinces. In conclusion, applying the revealed suggestions on improving the current situation will provide to gain for elevating the production of the province and region to the higher level.